When marketing is everyone's business: Entrepreneurs and the practice of marketing. Issue 1 (12th January 2015) - Unknown
Abstract : Purpose: – The purpose of this paper is to draw attention to opportunities for further research into the marketing practices of small entrepreneurial firms. Design/methodology/approach: – This study reviews the academic literature and identifies a gap in the existing research. It proposes the use of social practice theory in researching entrepreneurial marketing. Findings: – Entrepreneurship and marketing have a lot in common – especially in small firms (small to medium-sized enterprises [SMEs]). When there's nobody with a dedicated marketing role, then people all over the organization typically do things that contribute to the firm's marketing effort. And, when marketing becomes the sum of activities carried out by different individuals at different levels within the SME, it becomes "an all-pervasive way of doing business", rather like entrepreneurship, in fact. Research limitations/implications: – This study provides a conceptual overview of the benefits of applying social practice theory to the study of entrepreneurial marketing. Practical implications: – This study shows how social practice theory can be applied to the study of entrepreneurial marketing practices. Social implications: – This study explains how these marketing practices can be conceptualized to provide insights into the significance of marketing-related activities in small firms. Originality/value: – This study has the potential to facilitate the development of a new marketing research stream based on social practice theory.